2016
DOI: 10.1172/jci.insight.86955
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human skin microbiota in models of atopic dermatitis

Abstract: Atopic dermatitis (AD) is characterized by reduced barrier function, reduced innate immune activation, and susceptibility to Staphylococcus aureus. Host susceptibility factors are suggested by monogenic disorders associated with AD-like phenotypes and can be medically modulated. S. aureus contributes to AD pathogenesis and can be mitigated by antibiotics and bleach baths. Recent work has revealed that the skin microbiome differs significantly between healthy controls and patients with AD, including decreased G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 51 publications
(46 reference statements)
7
114
1
5
Order By: Relevance
“…AD severity was assessed using the SCORAD scale (20). Consistent with prior findings (16,17), enrollment cultures of the patients' antecubital fossae did not yield Gram-negative bacteria.…”
Section: R Mucosa Does Not Display Signs Of Toxicity In Micementioning
confidence: 74%
See 2 more Smart Citations
“…AD severity was assessed using the SCORAD scale (20). Consistent with prior findings (16,17), enrollment cultures of the patients' antecubital fossae did not yield Gram-negative bacteria.…”
Section: R Mucosa Does Not Display Signs Of Toxicity In Micementioning
confidence: 74%
“…Notably, these reports never assessed whether the isolates of R. mucosa associated with clinical symptoms could fulfill Koch's postulates for defining pathogens. Our previous work found that R. mucosa application to mouse skin that had undergone tape-stripping or chemical-induced dermatitis provided clinical benefit for the mice without any signs of toxicity (17). However, prior to clinical use we assessed the potential for systemic spread of R. mucosa to cause pathology by injecting mice intravenously with 10 3 , 10 4 , or 10 8 colony-forming units (CFU) of 3 HV-derived R. mucosa strains independently, a strain of R. mucosa (ATCC BAA-692) isolated from a clinical blood culture (19), or saline diluent alone.…”
Section: R Mucosa Does Not Display Signs Of Toxicity In Micementioning
confidence: 99%
See 1 more Smart Citation
“…Трансплантация фекального микробиома была успешной при кишечных заболеваниях, таких как рецидивирующий псевдомембраноз-ный энтероколит и болезнь Крона, но данные относительно АД отсутствуют [7,109,110].…”
Section: изменения микробиоты при заболеваниях кожиunclassified
“…Для восстановления кожно-го микробиома при AД можно использовать трансплантацию микробиоты от здоровых до-бровольцев. В мышиной модели AД культиви-руемые грамотрицательные бактерии, такие как Roseomonas mucosa от здоровых добро-вольцев, уменьшали рост S. аureus, улучша-ли барьерную функцию кожи и активирова-ли врожденную иммунную функцию [7,115]. В дальнейшем такая обработка может стать доступной для больных людей.…”
Section: изменения микробиоты при заболеваниях кожиunclassified